Migration behavior of fugitive methane in porous media: Multi-phase numerical modelling of bench-scale gas injection experiments - Bouznari, Kenza; Molson, John; Van De Ven, Cole J.C.; Mumford, Kevin G. (Advances in water resources, 2024)
•Numerical modelling of detailed laboratory experiments shows that a multiphase continuum approach can capture complex methane behavior.•Methane mass transfer kinetics are controlled by the water-gas interfacial area, especially in high velocity contexts.•Accurate values of entry pressure and residual saturation are critical for reliable methane migration simulations. Two-dimensional multi-phase numerical simulations based on detailed laboratory experiments are used to provide insight into the key processes of methane migration in porous media and to analyze the suitability of a continuum approach for modelling gas migration at the intermediate bench-scale. The simulations were conducted using the multi-phase numerical model DuMux, including groundwater flow, transport of free-phase methane subject to capillary and buoyancy forces, kinetic-controlled dissolution of methane into the flowing groundwater, and advective-diffusive transport of dissolved-phase methane. Mass transfer kinetics are controlled by the water-gas interfacial area, avoiding the assumption of thermodynamic equilibrium which was shown not applicable under these conditions of high aqueous velocity in sandy materials. The model is applied to a series of 2D laboratory experiments in which gas-phase methane was injected near the bottom of a 1.5 m square vertical flow cell under a background flow gradient and with homogeneous and heterogeneous configurations. Simulations are compared to the observed behavior with respect to gas-phase mass distribution over time, gas-phase saturations, and to breakthrough of the dissolved-phase methane at selected monitoring points. In this first comparative study (simulations vs real data), insights are provided into the role of spatial property distributions on methane migration, in particular gas-phase pooling below low-permeability layers. Similar to the laboratory results, the simulations confirmed that the concentrations of dissolved-phase methane are strongly dependent on the structure of the gas-phase plume which in turn is influenced by the geology. We show that at the local metre-scale, kinetic-controlled mass transfer is needed to reproduce the dissolved-phase methane concentrations. Nevertheless, an assessment of capillary parameter values typically encountered in sandy aquifer materials suggests that an equilibrium approach could still be suitable for field-scale simulations.